The functional role of root-associated microbiome and metabolome of myrothamnus flabellifolia - Tebele, Shandry Mmasetshaba (Department of Molecular and Cell Biology, 2026)
Global climate change is predicted to increase the occurrence and severity of drought, particularly in Africa, which will negatively impact crops and food production. Drought is the leading factor that adversely affects agricultural productivity and yield. Over the last four decades, extensive research on resurrection plants has yielded valuable insights into the mechanisms these plants employ to adapt during desiccation. Despite this, the role of the microbiome in desiccation tolerance, particularly in resurrection plants, remains a relatively unexplored area. Myrothamnus flabellifolia, a resurrection plant, stands out for its remarkable ability to endure severe desiccation, making it an ideal model for investigating the contributions of the plant microbiome to desiccation tolerance. Recognising the significance of root-associated microbes in stress tolerance opens up promising opportunities for enhancing drought resilience in crucial crops. However, the intricate dynamics of these interactions under severe water limitations have not been comprehensively investigated. Consequently, a primary objective of this study was to unravel the beneficial root-associated microbiome of M. flabellifolia and delineate their functions in the context of water deficit conditions. The intricate tripartite interplay involving plant roots, soil, and microorganisms remains enigmatic and demands further exploration. This study delved into the microbiome of belowground zones—bulk soil, rhizosphere soil, and endosphere of M. flabellifolia. Metagenomic analysis unveiled prevalent bacterial phyla (Acidobacteriota, Actinobacteriota, Chloroflexota, Planctomycetota, and Pseudomonadota) and dominant fungal phyla (Ascomycota and Basidiomycota) across all zones. While the bulk soil hosted numerous beneficial root-associated microbes, it exhibited lower functional diversity than the rhizosphere, which showcased the highest diversity of bacteria and fungi. Conversely, the endosphere exhibited lower microbial abundance and diversity. These findings suggest that M. flabellifolia may recruits soil microbes from bulk soil to rhizosphere and subsequently to the endosphere. Metatranscriptomic analysis has revealed crucial insights into the dynamics of plant-microbe interactions and the adaptive mechanisms employed by root-associated bacteria during desiccation in M. flabellifolia. The transcriptional activity of bacteria involved both monoderm and diderm lineages, consistent with the bacterial phyla identified in metagenomic analysis. However, the dominance of the Pseudomonadota phyla at the transcriptional activity was observed. Root-associated bacteria showed distinct transcriptional responses during dehydration and rehydration, suggesting dynamic shifts in microbial activity under fluctuating water availability. The expression of differentially expressed genes (DEGs) under dehydration conditions showcased the activation of proteins associated with antioxidant enzymes, molecular chaperones, protein kinases, and biosynthesis of sugars and amino acids. This implies a coordinated response to counteract damage and enhance survival. Intriguingly, the upregulation of genes encoding protein kinases, antioxidant enzymes, and trehalose synthase in root-associated bacteria reflects a common strategy for surviving desiccation stress. This suggests a potential case of convergent evolution in desiccation tolerance within microbiomes. The observed upregulation of genes related to plant growth and enhanced plant-microbe interaction under rehydration conditions suggests a resumption of microbial activity. Exploring the rhizosphere soil metabolome provided insights into the metabolic changes during drought stress in M. flabellifolia. Dehydrated rhizosphere soil exhibited increased levels of sugars (e.g., trehalose), organic acids (malic acid), and phytohormones (indole-3-acetic). Conversely, rehydrated rhizosphere samples showed significantly higher amino acid levels compared to desiccated samples, indicating a shift in biochemical processes in both the plant roots and rhizosphere microbiome. While rhizosphere metabolites are typically attributed to root exudates and microbial activity, this study revealed that many were possibly produced by rhizospheric bacteria. The upregulation of bacterial genes associated with metabolite biosynthesis under dehydration conditions, such as trehalose, further substantiated the the notion that drought serves as a selective pressure driving convergent evolution in species with desiccation tolerance. These findings indicates that the microbiome's adaptability under harsh environmental stress. Furthermore, inoculating maize plants with rhizospheric bacteria from M. flabellifolia's rhizosphere significantly improved drought tolerance, physiological, and morphological traits. The study concludes that root-associated microbiomes play a crucial role in M. flabellifolia's desiccation tolerance and plant growth-promoting microbes have a potential to be used as a biostimulant. This innovative research has implications for enhancing food security, developing resilient agricultural systems, and promoting sustainability.